Abracadavers. Season 1 [videorecording (DVD)] - Ermter, Morgan; Cork, Griffin; Schwartz, Alanna; Pritchard, Danae; Harder, Ethan; Haugan, Rachael; Belot, Aaron; Houghton, Emma; Wright, Jordan (Octane Multimedia, 2022)
After the death of his Mom, Chris developed an unhealthy obsession with the hair salon chair that killed her. On a forced road trip with his friends, things get weird when the group discovers the chair might be giving them superpowers.